Study transit network design for Rivera of Uruguay. Issue 8 (17th November 2017) - Chao, Henry
Abstract: We offer a complete examination for the paper of Mauttone and Urquhart that was published in Computers & Operations Research, Vol. 36, No. 8, 2440-2449 (2009), for a route set construction algorithm for the transit network design problem of the city Rivera, Uruguay. We point out several questionable results in Mauttone and Urquhart (2009) and then we provide possible revisions for those dubious findings that will help researchers develop better transportation plan in the future.